Identification of a genetic marker for isometamidium chloride resistance in Trypanosoma congolense - Delespaux, V.; Geysen, D.; Majiwa, Phelix A.O.; Geerts, S. (Elsevier, 2005)
Isometamidium chloride has remained a very important prophylactic and therapeutic drug against trypanosomosis in cattle since its introduction into the market in the 1950s with, unfortunately, a concomitant development of resistance in trypanosomosis endemic areas. Amplified Fragment Length Polymorphism (AFLP) was used to compare two isogenic clones of Trypanosoma congolense. The parent clone, sensitive to isometamidium, has a CD50 (the curative dose that gives complete cure in 50% of the animals) in the mouse of 0.018 mg/kg and its derivative exposed to increasing doses of isometamidium, has a CD50 that is 94-fold higher. Sixty-four combinations of eight Eco RI and eight Mse I primers were used in comparative AFLP analysis to detect subtle genetic differences between the two clones. Thirty-five polymorphic fragments of DNA that were observed only in the resistant clone were purified and then sequenced. The nucleotide sequences were used in searching the GeneDB T. congolense database to find surrounding sequences upstream of an open reading frame and downstream to a stop codon. The sequences of the open reading frames were subsequently compared to the sequences in the genomic databases. A predicted gene coding for an 854 amino acids protein was thus identified. The protein contains a putative ATP binding site, Walker B and LSGG motifs and eight predicted trans-membrane domains. The gene in the resistant strain of T. congolense has a triplet insertion coding for an extra lysine. Using polymerase chain reaction-restriction fragment length polymorphism, the insertion was sought in the genomes of 35 T. congolense strains isolated from different geographic origins and whose response to isometamidium chloride had been determined through single dose mouse tests. The presence of the insertion, specifying an extra codon was found to always be present in the genomes of T. congolense clones that were resistant to isometamidium chloride.